Children Fleeing Domestic Violence to Emergency Accommodations: Education Rights and Experiences - Selvik, Sabreen (Journal of family violence, 2021)
Domestic violence forces many families to flee to emergency accommodations. This article focuses on children’s experiences of schooling and life at confidential addresses, and to what extent their legal right to education in the face of domestic violence is safeguarded in practice. Data were collected from interviews with 20 children aged 6–16 with multiple relocations at Norwegian refuges for abused women. Interviews were coded using the constructive approach to grounded theory. Data were analyzed using Antonovsky's theory and interpreted within the context of Norwegian and international law, examining the rights of children to education versus the legal rights of abusers. The findings indicate that children’s rights to education and a life without violence may be sacrificed in favor of due process for abusers. The article suggests concrete protective measures to help safeguard these rights, and calls on policymakers and support agencies worldwide to rethink their policies and practice.